PROFIT MANAGEMENT ANALYSIS: THE ROLE OF PROFITABILITY AND LEVERAGE IN LQ-45 COMPANIES - Hani, Syafrida; Winanda, Yola; Pratama Marpaung, Arif (CERED Indonesia Institute, 2025)
In this approach, the author uses a quantitative associative approach that aims to determine the causal influence of the variables studied. The data presented are numbers and analyzed using statistics. The population used in this study is the entire population of LQ-45 companies from 2017-2021, totaling 45 companies. The sample was determined based on a purposive sampling method, namely by taking a sample of companies during the research period based on certain criteria. Based on the criteria, the sample in this study was 21 LQ-45 companies. The data analysis technique used in this study is data that is sought simultaneously by obtaining it outside the company. In this study, data collection was carried out using a documentation study technique. Meanwhile, the data analysis techniques used are multiple linear regression, classical assumption tests, t-tests, f-tests, and coefficients of determination. Partially, Profitability has a significant effect on Earnings Management. Partially, Leverage has a negative and insignificant effect on Earnings Management. Simultaneously, the results obtained in this study are that the variables of Profitability and Leverage do not affect Earnings Management in LQ-45 Companies Listed on the Indonesia Stock Exchange for the 2017-2021 period.